2017
DOI: 10.1111/pace.13063
|View full text |Cite
|
Sign up to set email alerts
|

High Patient Satisfaction with Deep Sedation for Catheter Ablation of Cardiac Arrhythmia

Abstract: The results of our study show that deep sedation during catheter ablation of cardiac arrhythmias is generally well tolerated and patients are satisfied with the procedure. Yet, a number of patients reports pain or adverse events. Therefore, studies comparing different sedation strategies should be conducted in order to optimize sedation and analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Moreover, these patients could also benefit on patient satisfaction and possible reduction of hospitalization time. The last one has been demonstrated in a series of patients undergoing cardiac surgery where the use of hypnosis in the pre and post-operative period was able to reduce hospitalization time [[13], [14], [15]].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these patients could also benefit on patient satisfaction and possible reduction of hospitalization time. The last one has been demonstrated in a series of patients undergoing cardiac surgery where the use of hypnosis in the pre and post-operative period was able to reduce hospitalization time [[13], [14], [15]].…”
Section: Discussionmentioning
confidence: 99%
“…Our results expand the options for anesthesia strategy during PSVT ablation beyond minimal sedation, and we expect it to lead to greater patient satisfaction. 2 patients with ectopic AT, the tachycardia terminated after propofol infusion and could not be induced by ISP. 19 Theoretically, if the mechanism of AT is abnormal automaticity or triggered activity, its inducibility can be decreased by deep sedation that reduces sympathetic nerve activity.…”
Section: Need Of Deep Sedation For Psvt Ablationmentioning
confidence: 90%
“…This disadvantage is further supported by Narui et al, 22 in which patients with mild sedation endured pain and uncomfortable conditions during procedure. A survey by Münkler et al 30 also demonstrated a high patient satisfaction with deep sedation, with 83% of patients considering it to be 'good' or 'very good'.…”
Section: Safety and Concerns Regarding Ga/deep Sedation And Consciousmentioning
confidence: 97%